Structural Transformation, Service Sector Growth and Poverty Alleviation: The Role of Formal–Informal Interaction and Rising Informal Wage. Issue 2 (December 2020) - Marjit, Sugata; Sasmal, Ritwik; Sasmal, Joydeb
The motivation of this article is to develop a theoretical mechanism on the interaction between formal and informal sectors and rising informal wage, in the process of service sector growth. Based on empirical support for service sector growth, structural change, higher employment of labour in unorganised sector and rising informal wage in the Indian context, this article develops a theoretical model on the formal–informal interaction in labour employment using a trade-theoretic general equilibrium framework. The results show that with the expansion of capital-intensive, organised service sector, following capital investment in the country, the informal, non-traded intermediate sector, which supplies inputs to the formal service sector, expands with greater employment. The labour-intensive domestic sector of consumer services declines, with the result that the price of consumer services rises, leading to rise in informal wage rate.